Cholangiocarcinoma of intrahepatic bile ducts with disseminated metastases in a Siamese cat: a case report - O. Aslan; L. Cakir; I.K. Bekdik; Z. Dogan; A.S. Tunc (Veterinární Medicína, 2014)
This case report concerns a four-year-old female Siamese cat which presented with inappetence, vomiting and weight loss. During routine clinical examinations of the patient, numerous neoplastic masses were detected in the liver, lungs and abdomen. Upon a request from the owner, the cat was euthanised. At necropsy, the primary tumour was detected in the liver. The tumour was greyish-white, firm, and multi-nodular. There were metastases in the portal lymph nodes, diaphragm, omentum, colon, caecum and lungs. Histologically, the tumour was characterised by a tubular pattern with periodic acid-Schiff- positive secretory material in glandular and canal structures. The neoplastic cells were positive to broad-spectrum cytokeratin. Histochemical and immunohistochemical stains were consistent with an intrahepatic bile duct carcinoma. This is the first case to report the metastasis of a cholangiocellular carcinoma to the colon in cats.